Experimental Study on the Impact of Landslide-Generated Waves against Wharf Pile - Ping Mu; Pingyi Wang; Linfeng Han; Jie Zhang; Meili Wang (Advances in Civil Engineering)
Landslide-generated waves have caused great catastrophic damage to the infrastructure, e.g., dam and wharf, because of the extreme loading in the reservoir area, while the wharf pile is rarely designed to withstand the loading associated with landslide-generated waves. This experimental study was conducted in a generalized 3D basin to simulate the waves generating process and explore the impact of the dynamic pressure process on the wharf pile. As the phenomenon that landslide-generated impulse waves impacted on the wharf pile in the form of dynamic pressure, the distribution pattern of the dynamic pressure along the water column was analyzed and revealed specifically. The results indicate that the dynamic pressure was constant below the water surface along the vertical direction and its magnitude was correlated with the wave amplitude as well as wave celerity. On this basis, a multivariate dimensionless analysis was implemented, and the empirical formulas for the dynamic pressure were established. Furthermore, the total force acting on the wharf pile was given. From a practical perspective, these findings could offer guidance to prevent the damage of the impulse wave pressure on the wharf pile.